Vesicouterine fistula presenting with urinary incontinence 30 years after primary Cesarean: Case report and review of the literature - Gungor Ugurlucan, Funda; Bastu, Ercan; Bakir, Baris; Yalcin, Onay (Canadian Urological Association Journal, 2014)
A vesicouterine fistula is an abnormal communication between the bladder and the uterus. The most common cause is lower segment Cesarean section. Conservative treatment may be applied in some cases, but surgery is the definitive treatment. We present a 55-year-old woman with vesicouterine fistula after primary Cesarean section; she presented with urinary incontinence 30 years later. Methylene blue dye test was performed and drainage of urine dyed with methylene blue through the uterine cervix was observed. Diagnosis was confirmed with magnetic resonance imaging. Total abdominal hysterectomy and bilateral oophorectomy was performed and the bladder wall was sutured in a double layer with 2/0 polyglycolic suture. No complications developed and the patient did not suffer from any urinary incontinence afterwards. Vesicouterine fistula should be suspected in cases presenting with urinary incontinence even years after Cesarean section; diagnostic tests and, if necessary, appropriate surgery should be performed.